Virginia Woolf: Lesbian readings - Barrett, Eileen; Cramer, Patricia (New York University Press, 1997)
The last two decades have seen a resurgence of critical and popular attention to Virginia Woolf's life and work. Such traditional institutions as The New York Review of Books now pair her with William Shakespeare in promotional advertisements; her face is used to sell everything from Barnes & Noble books to Bass Ale. Virginia Woolf: Lesbian Readings represents the first book devoted to Woolf's lesbianism. Divided into two sections, Lesbian Intersections and Lesbian Readings of Woolf's Novels, these essays focus on how Woolf's private and public experience and knowledge of same-sex love influences her shorter fiction and novels. Lesbian Intersections includes personal narratives that trace the experience of reading Woolf through the 60s, 70s, 80s, and 90s. Lesbian Readings of Woolf's Novels provides lesbian interpretations of the individual novels, including Orlando, The Waves, and The Years. Breaking new ground in our understanding of the role Woolf's love for women plays in her major writing, these essays shift the emphasis of lesbian interpretations from Woolf's life to her work.
Keywords: approches et analyses; arts; discipline; europe; lesbianisme; littérature; royaume-uni; régions géographiques; études littéraires

Construction du sujet-femme et imaginaire dissident : Largo desolato de Václav Havel - Deret, Anne (Université du Québec à Montréal, 1997)
Keywords: 1900-1999; 1980-1989; IREF; discipline; europe; mémoires/thèses; périodes historiques; régions géographiques; république tchèque; science politique; théâtre

Les lesbiennes et le roman français 1796-1996 - Waelti-Walters, Jennifer (Nouvelles Questions Féministes, 1997)
La lesbienne telle qu'on la connaît aujourd'hui est entrée dans le roman français avec La Religieuse de Diderot (pub. 1796), et jusqu'en 1926 elle est créée et recréée presqu'exclusivement par les écrivains hommes qui modèlent leurs personnages sur Margarita de La Fille aux yeux d'or de Balzac et Mademoiselle de Maupin de Gautier, pour en faire des femmes menaçantes pour la virilité collective. A partir de 1930 les expériences littéraires lesbiennes sont prises en charge par des auteures femmes qui en explorent les secrets, les misères et les oppressions d'abord, et ensuite — à partir de l'oeuvre de Monique Wittig et de Jocelyne François — la vie quotidienne dans sa variété. Cet article est un compte rendu d'unprojet de recherche en cours — projet qui étudie un territoire littéraire jusqu'ici totalement ignoré dans l'histoire du roman.
Keywords: approches et analyses; arts; discipline; discours dominant; europe; france; histoire du roman; hétérosexisme; patriarcat; personnes lesbiennes; régions géographiques; systèmes d'oppression; études littéraires

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; discipline; europe; fem1000; histoire et politique; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires